A framework for enchancing emotion and usability perception in design - Seva, Rosemary R. (Animo Repository, 2008)
The study proposes a design framework that may be used in the conceptualization stage. The Usability Perception and Emotion Enhancement Model (UPEEM) combine the concepts of emotional quality and apparent usability in promoting the desirability of the product. The model posits that the perception of selected product attributes influence the perception of apparent usability and emotional quality of the product that are important in determining the product's desirability. Furthermore, the model proposes that apparent usability also affects the emotional quality of the product. The model was conceptualized from earlier studies on apparent usability and affective design. Previous research has identified the connection between product attributes and emotional quality but usability was not considered. These two are important aspects of product design and it is deemed important to know the relationship of these two in promoting the desirability of the product. The model may be used in identifying product attributes that are important in design. Keywords: affective product design, mobile phone design, product design